Electrolysers for producing net-zero heat. Issue 6 (June 2021) - Newborough, Marcus; Cooley, Graham
Abstract : In addition to fuel cell applications, water electrolysis affords several opportunities for producing high-grade heat by utilising electrolytic hydrogen and oxygen in combustion applications. This can reduce or eliminate the atmospheric emissions associated with the combustion of conventional fuels. Importantly, net-zero heat can be produced if the electrolyser is powered by renewable electricity, whereby the output gases may be termed green hydrogen and green oxygen. This paper provides an overview of prospective applications for electrolysers in the heat sector by considering three general implementation pathways based on how the electrolytic oxygen is used.